Counselling for depression - Sanders, P.; Hill, A. (London British Association for Counselling & Psychotherapy Thousand Oaks, CA Sage Publications Ltd, 2014)
The first book to take a humanistic - person-centred/experiential - approach to counselling to the most commonly presenting client issue, depression. A landmark text, covering everything from evidence-based practice to training, supervision and research, it establishes humanistic counselling as an evidence-based psychological intervention--
Introduction -- Evidence-based practice and person-centred and experiential therapies -- Introducing the counselling for depression competence framework -- Depression -- Person-centred and experiential therapies -- Conceptualising depression from a person-centred and experiential therapies perspective -- Working briefly -- The counselling for depression therapeutic stance and auxiliary techniques -- Counselling for depression in practice -- Training, supervision and research: developing counseling for depression.
Keywords: Depressed persons; Depression; Counseling; Patient-Centered Care; Depressed persons; Depression; Nichtdirektive Psychotherapie; Psychologische Beratung